A3.19 mIR-193B induces UPA in SSC and contributes to the proliferative vasculopathy via uPAR independent pathways. (31st January 2014) - Iwamoto, Naoki; Vettori, Serena; Maurer, Britta; Brock, Matthias; Jüngel, Astrid; Calcagni, Maurizio; Gay, Renate E.; Distler, Jörg H. W.; Gay, Steffen; Kawakami, Atsushi; Distler, Oliver
Abstract : Background: We had reported that miRNA-193b (miR-193b) is significantly downregulated in SSc and that down regulation of miR-193b causes overproduction of urokinase type plasminogen activator (uPA). However, the effects of increased levels of uPA may be limited in SSc because of inactivation of the cellular receptor for uPA (uPAR) after cleavage by matrix metalloproteinase-12. Objective: To investigate whether the effects of uPA in SSc are mediated by uPAR independent pathways. Methods: Expression of miR-193b in SSc skin fibroblasts and skin sections from SSc were analysed by Real-time PCR. Transfection with miR-193b precursor and inhibitor were used to identify targets of miR-193b. Basal expression and localisation of uPA were examined by Real-time PCR, Western blot and immunohistochemistry. Furthermore, human pulmonary artery smooth muscle cells (HPASMCs) were treated with uPA and the proliferative effects of uPA were determined by WST-1 assay and by analysis of proliferating cell nuclear antigen expression. FACS was performed to investigate the effect of uPA on apoptosis. For inhibition of the uPA-uPAR pathway, uPAR neutralising antibodies, siRNA against uPAR and low molecular weight uPA, which does not bind to uPAR, were used. Results: MiR-193b was significantly down regulated in SSc fibroblasts (n = 12) as compared with healthy controls (HC) (n = 6) (31 ± 33%, p<0.01). In addition, miR-193b was also reduced in SSc skin sections (n = 5) as compared with HC (n = 5) (54 ± 16%, p<0.005). Induction of miR-193b in SSc fibroblasts suppressed the production of uPA protein and the expression of uPA mRNA. Conversely, knockdown of miR-193b increased the level of uPA expression. Under TGF-b stimulation, the expression of uPA in SSc fibroblasts was upregulated as compared with HC (x-fold induction: 8.5 ± 3.9, P<0.05). uPA was expressed preferentially in vessel in SSc skin sections. Interestingly, uPA induced cell proliferation (121 ± 23.8%, P<0.05) and inhibited apoptosis (by 66 ± 3.9%, P<0.05) in HPASMCs. Even in the presence of uPAR neutralizing antibodies or after silencing of uPAR by siRNA, uPA effectively inhibited apoptosis (80 ± 6.4% and 82 ± 19.2% respectively, P<0.05 both). Finally, low-molecular uPA also inhibited apoptosis significantly (79 ± 5.9%, P<0.05) confirming the results with neutralizing antibodies and siRNA. Conclusion: Our results suggest that the down regulation of miR-193b in SSc induces expression of uPA, which leads to increased numbers of vascular smooth muscle cells via uPAR independent pathways and thereby contributes to the proliferative vasculopathy characteristic of SSc. This is the first link between miRNA dysregulation and vasculopathy in SSc.